An Investigation of the Supply Chain Strategy for Social Carrying Capacity: A Study of Pangkor Island, Perak, Malaysia - Yusoh, Mohamad Pirdaus; Mapjabil, Jabil; Hanafi, Nurhazliyana; Abdullah, Ahmad Niza Syazre; Muhammad, Zikri (ExcelingTech, 2020)
Tourism is one of the fastest-growing sectors and plays a vital role in economic development in most countries, including Malaysia. With an extraordinary growth of tourist arrival, it has given effect on the environment, social and economic structures. Of these, the primary purpose of the current study is to identify the perception of domestic tourists on the intensity of social carrying capacity at Pangkor Island, Perak, Malaysia. This quantitative study is designed using a survey questionnaire (self-administered) to 332 domestic tourists during four phases of public holidays as a tourist option to visit Pangkor Island. The results of this study indicated that the Social Carrying Capacity (SCC) assessment is based on tourists' response, crowding rate at a tourist spot/location and the satisfaction level of tourists while travelling to the area. The perception of domestic tourists is divided into three parts, namely; satisfaction with the facilities, quality of experience and acceptance from the locals. Also, using the People at One Time (PAOT) method, respondents were given five options and picture showing the tourist situation during their visit to Pulau Pangkor. From PAOT analysis, 37.5% tourists chose Picture C followed by picture D (31.2%), Picture B (11.8%), picture E (8.1%), Picture F (7.7 %) and picture A (3.7%). As a result, from these two methods, SCC in Pangkor Island is still acceptable for domestic tourists. This study provides significant information to stakeholders to make sure that SCC at Pangkor Island is within tourism activities control.Keywords—Social Carrying Capacity, Tourism Carrying Capacity, Intensity